Power, policy, and the ideology of punishment: time series analysis of the U.S. political economy of punishment in the race to incarcerate, 1972-2002 - Jackson, Henry Jr. (Kansas State University, 2009)
This study seeks to explain variation in incarceration rates across states. To account for such variation, the study combines approaches: the Rusche & Kirchheimer (1939) thesis, which proposes that incarceration rates rise with unemployment due to potential threat to social order from the unemployed, was merged with social stratification theories to develop a theoretical model explaining variations in state incarceration rates by social class and race. The last 30 years have seen a number of studies dedicated to investigating the validity of the Rusche and Kirchheimer (1939) thesis, but these studies have yielded inconsistent results. This study adheres to and advances Rusche and Kirchheimer’s thesis, exploring the relationship between unemployment rates and incarceration rates utilizing nationwide state-level data. I tested the influence of economic factors on prison rates across the nation interacting with race-ethnicity using time series hierarchical regression, and data indicates mixed support for the Rusche and Kirchheimer thesis. This study found that important predictors related to rising incarceration rates include citizen and governmental political ideology, violent and property crime rates, and percent of population that is African American. Habitual violation of laws, including drug crime, and poverty had small effects on the incarceration rate. Additionally, this study found that inequality, not unemployment, was the most salient predictor of incarceration rates; that is, the differential in employment pay rate factored more significantly than the designation of employed/unemployed. The study revealed that such a relationship between income inequality and punishment differentially impacts citizens in general and African Americans in particular. Since excessive use of prisons exacerbates inequality, understanding the link between economic conditions such as income inequality and punishment has notable policy implications.
Keywords: Punishment; Race; Sociology, Criminology and Penology (0627)